(untitled) (Journal of Governance and Development (JGD), 2021)
The publication proposes the governance for the organisations in the development of the 21st century. Further, a qualitative study on Knowledge Management (KM) in Higher Educational Institutions (HEIs) discovered the bases of governing Institutions from the perspective of HEIs. Meanwhile, the research on Knowledge Management (KM) grounded the fact relevant to the governance in the organisation in the KM era such as benchmarking to be competitive in the industry while preserving the business composition and aligning courses with National budget proposals to enhance employability. Accordingly, the present publication recognised those likewise facts and composed those discovered facts as the governance for the organisation in the KM era based on the standard that the institution is an organisation. Further, the discovery of the governance for the organisation is based on the definition of KM practices of HEIs and the conceptualisation of the governance for the organisation. Besides, the present study tested the KM practices of HEIs presented in the postgraduate revelation to satisfy the conceptualising of the governance of the organisation. Further, the present test recognised the KM practices of HEIs as the governance of the organisation. Accordingly, the present publication proposes organisational governance in the development of the 21st century.